GROWING UP COMING GENERATION IN HEALTH ENDOCRINE OF FACTORS ROLE AND CURRENT DANGERS - Bekmetova Shokhida Kadirberdiyevna , Nematova Sitara Sokhib kizi (International Journal of Literature and Language Studies, 2026)
This in the article grow coming generation in health endocrine system caught place and hormonal disorders in child development impact illuminated . Research during thyroid diseases (Hashimoto) , diabetes diabetes , growth​ hormone deficiency ( nanism ) and modern medicine current problem was metabolic syndrome come exit reasons and clinical signs analysis Also , puberty during the period physiological changes and hormonal imbalance cognitive and physical in development dangers based on given . In the article endocrine pathologies early determination and healthy​ marriage style of formation strategic importance is emphasized .